PEMBELAJARAN PENGALAMAN DALAM MEWUJUDKAN TRANSFORMASI SOSIAL DAN KEBANGKITAN SPIRITUAL BAGI KALANGAN PEMUDA-PEMUDI BUDDHIS INTERNASIONAL: STUDI EMPIRIS PADA PROGRAM BODHISATTVA MUDA INTERNASIONAL DI TAIWAN TAHUN 2025 - Purnomo, Dwi (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
This study aims to explore the experiential learning process within the International Young Bodhisattva Program 2025, organized by the International Network of Engaged Buddhists (INEB) at Hongshi Buddhist College, Taiwan. This program is designed to develop a cross-national generation of young people with social awareness, deep spirituality, and practical skills for realizing social transformation. The research approach used was a descriptive qualitative case study method. Data were collected through participant observation, in-depth interviews, and activity documentation. Data analysis was conducted inductively through data reduction, presentation, and conclusion drawing. The results indicate that this program has a significant impact on the development of social awareness, spiritual transformation, and cross-cultural collaboration. This program serves as an alternative educational model that integrates spirituality, critical reflection, and social action, in line with the contemporary transformative education paradigm.